Methodological procedures for ultrasonographic assessment of the tongue during sucking in full-term infants: A scoping review - Anna Fernanda Ferreira de Alves Melo; Roberta Lopes de Castro Martinelli; Rodrigo Alves de Andrade; Ana Paula Alves Figueiredo Lima; Aline Natallia Simões de Almeida; Anna Clara Mota Duque; Daniele Andrade da Cunha; Hilton Justino da Silva (BMC Pediatrics)
Abstract Background This scoping review aimed to identify methodological procedures for acquiring and analyzing ultrasound images of the tongue during sucking in full-term infants. The Participants, Concept, and Context strategy was used to define the inclusion criteria: population (full-term infants); concept (ultrasound assessment); and context (assessment of tongue movements during sucking). Methods It included observational, experimental, descriptive, and analytical studies, and excluded those unavailable in full, with premature infants, babies with craniofacial changes and syndromes, studies on animals, in vitro, letters to the editor, errata, and using ultrasound for other purposes. There were no language or time restrictions. Two blinded professionals independently selected 20 articles that met the inclusion criteria from different databases. Results The most evaluated parameters were related to the morphometric and kinematic aspects of the tongue, considering the physical behavior of the nipple and bottle nipple; sucking, swallowing, and breathing; distance from the tip of the nipple to the hard-soft palate junction; and milk flow. An endocavity transducer was positioned in the submental region at 5 MHz to 8 MHz.  Conclusions The studies present the acquisition and static analysis of ultrasound images of the tongue, hard and soft palate, nipple, and bottle nipple, and of kinematic measurements of the tongue, nipple, bottle nipple, and hyoid bone. They evaluated quantitative and qualitative parameters. Frequency adjustment depended on the child’s age (the B mode was the most used), with babies reclined on the mother’s lap to feed from the mother’s breast and/or bottle.